2012
DOI: 10.5505/tjb.2012.21043
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hemolysis on the assays of serum CK, CK-MB activities and CK-MB (MASS), troponin and myoglobin measurments

Abstract: Aim: The aim of the study was to investigate the effects of in vitro hemolysis on serum creatine kinase and creatine kinase MB isoenzyme activities with creatine kinase MB mass, troponin I and myoglobin measurements. Materials and methods:We prepared serum pools having analyte concentrations at normal and pathological values. Hemolysate was added into serum pools to obtain aliquotes with final hemoglobin concentrations of 21, 10.5, 5.25, 2.625, 1.312, 0.656, 0.328, 0.164, 0.08 and 0.041 g/L. Creatine kinase (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(19 reference statements)
2
0
0
Order By: Relevance
“…The mechanisms behind the hemolysis interferences include the additive interferences of released intracellular substances (eg, LDH, AST, K, and HBDH) and the chemical interferences when the released substances interacted with the measured analyte (eg, CK and CKMB); it was reported that intracellular adenylate kinase might interfere with the CK assay . In addition, our results showed that positive hemolysis interferences on CK‐MB activity started to increase at lower HI values compared with CK activity, which was in accordance with Oğuzhan Özcan's study . The reason may be that the errors from the interfering agents released by hemolysis were amplified by multiplying a constant; this constant parameter is commonly used to calculate the CKMB activity in the assay.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The mechanisms behind the hemolysis interferences include the additive interferences of released intracellular substances (eg, LDH, AST, K, and HBDH) and the chemical interferences when the released substances interacted with the measured analyte (eg, CK and CKMB); it was reported that intracellular adenylate kinase might interfere with the CK assay . In addition, our results showed that positive hemolysis interferences on CK‐MB activity started to increase at lower HI values compared with CK activity, which was in accordance with Oğuzhan Özcan's study . The reason may be that the errors from the interfering agents released by hemolysis were amplified by multiplying a constant; this constant parameter is commonly used to calculate the CKMB activity in the assay.…”
Section: Discussionsupporting
confidence: 90%
“…In conclusion, this is the first study to our knowledge that investigated HI thresholds using the Advia 2400 analyzer, which extended these HI studies . Our results provide HI thresholds for eight analytes (CKMB, CK, K, AST, HBDH, TBA, Na, and UA).…”
Section: Discussionsupporting
confidence: 54%